(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
These developments have the great advantage of providing interactive, graphical interfaces that can speed up your understanding and be especially appealing to children. So, while technology platforms make piano and piano learning more fun, learning from a studio teacher will make your learning journey even more inspiring. In fact, even the best option for you will be imperfect. So let’s take a look at your choices together and weigh the pros and cons of each.